The Therac-25: 30 Years Later - Leveson, Nancy G. (Computer (Long Beach, Calif.), 2017)
A widely cited 1993 Computer article described failures in a software-controlled radiation machine that massively overdosed six people in the late 1980s, resulting in serious injury and fatalities. How far have safety-critical systems come since then?